The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ijgi5110197
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Urban Growth Using GIS and Remote Sensing: A Case Study of the Colombo Metropolitan Area, Sri Lanka

Abstract: Abstract:Understanding urban growth spatiotemporally is important for landscape and urban development planning. In this study, we examined the spatiotemporal pattern of urban growth of the Colombo Metropolitan Area (CMA)-Sri Lanka's only metropolitan area-from 1992 to 2014 using remote sensing data and GIS techniques. First, we classified three land-use/cover maps of the CMA (i.e., for 1992, 2001, and 2014) using Landsat data. Second, we examined the temporal pattern of urban land changes (ULCs; i.e., land cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 61 publications
3
79
0
Order By: Relevance
“…Compared with other papers, the FoM value is above 30%, but this was from considering only two classes in LULC; for our research, there were 5 LULC categories with a FoM of 14.73%. This value demonstrated that the simulation result was well recognized [16].…”
Section: Model Validationsupporting
confidence: 55%
See 1 more Smart Citation
“…Compared with other papers, the FoM value is above 30%, but this was from considering only two classes in LULC; for our research, there were 5 LULC categories with a FoM of 14.73%. This value demonstrated that the simulation result was well recognized [16].…”
Section: Model Validationsupporting
confidence: 55%
“…All the images were processed with a spatial resolution of 30 m. In the ArcGIS 10.2 software, the pixel-based supervised classification technique employing the maximum likelihood classification algorithm was used to perform classifications [16]. In order to analyze the characteristics of urbanization in Tianjin city at the series of time from 1995 to 2015, the study area was aggregated into five types of LULC: Built-up, Cropland, Grass, Forest, and Water.…”
Section: Lulc Classificationmentioning
confidence: 99%
“…Water includes rivers and lakes. Landsat images were exploited to extract classified land use/cover maps by using maximum likelihood supervised classification method in ArcGIS 10.2 software [44]. Maximum likelihood supervised classification is based on using training samples to assign a pixel to the most appropriate land use/cover class with highest probability of pixels and assign the pixels to the land use/cover categories [45].…”
Section: Land Use/cover Mappingmentioning
confidence: 99%
“…Spatial-temporal modeling is the process of extracting hidden and useful knowledge from large-scale spatial and temporal datasets and has been widely applied in geo-information related fields [2][3][4]. Geographically weighted regression (GWR), which originated from local weighted regression approaches, has been widely used to address spatial non-stationarity issues [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%